An investigative study on the formation of AuNP embedded PS-b-PAA worms. - Tay, Shara Ming Yin. (2010)
Diblock copolymer can form aggregates of different morphologies in solution. In particular, the formation of gold embedded PS144-b-PAA28 worms in DMF-water mixtures is explored in this report. Two methods to produce the worm-like aggregates are discussed. The first method involves the formation of PS144-b-PAA28 worms from PS-SH stabilized gold nanoparticles (AuNP) while the second method involves the transformation of vesicles to worms. In the first method, hydrochloric acid (HCl) was added to induce the morphological change from spherical micelles to worms. The addition of HCl would reduce the inter-corona repulsion in the poly(acrylic acid) by protonating the carboxylic acid groups thereby causing the morphological changes. In the second method, the vesicle-to-worm transformation was induced by increasing the DMF content in solution. At a higher DMF/water ratio, the stretching of the polystyrene block in PS-b-PAA decreases to induce the morphological changes. A proposed mechanism for the vesicle-to-worm transformation is also presented.